Effect of freezing and cool storage on carotenoid content and quality of zeaxanthin-biofortified and standard yellow sweet-corn (Zea mays L.) - Calvo Brenes, Paula (2020)
Influence of freezing temperature at –20 °C and −80 °C up to three months, and influence of storage at 4 °C up to fifteen days on carotenoid content and quality parameters in zeaxanthin-biofortified and commercial yellow sweet-corn were evaluated. Cobs frozen and stored at -20 °C showed a decrease in carotenoid concentration, in which carotenoids from the β-branch were mainly affected, compared to the α-branch carotenoids. Freezing temperature at −80 °C did not affect carotenoid concentration for cobs stored up to three months. Storage at 4 °C was shown to be adequate for carotenoid retention up to fifteen days, and also as a preconditioning temperature to avoid the detrimental effects of storing cobs at −20 °C. Colour and starch content were not affected by storage at 4 °C up to fifteen days, however a reduction in sugars and total soluble solids was observed.